Changing the name of diabetes insipidus: a position statement of The Working Group for Renaming Diabetes Insipidus. Issue 11 (14th October 2022) - ,; Arima, Hiroshi; Cheetham, Timothy; Christ-Crain, Mirjam; Cooper, Deborah; Gurnell, Mark; Drummond, Juliana B; Levy, Miles; McCormack, Ann I; Verbalis, Joseph; Newell-Price, John; Wass, John A H
Abstract : ' What's in a name? That which we call a rose/By any other name would smell as sweet' (Juliet, from Romeo and Juliet by William Shakespeare). Shakespeare's implication is that a name is nothing but a word, and it therefore represents a convention with no intrinsic meaning. While this may be relevant to romantic literature, disease names do have real meanings, and consequences, in medicine. Hence, there must be a very good rationale for changing the name of a disease that has a centuries-old historical context. A working group of representatives from national and international endocrinology, and pediatric endocrine societies now proposes changing the name of 'diabetes insipidus' to 'arginine vasopressin deficiency (AVP-D)' for central etiologies, and 'arginine vasopressin resistance (AVP-R)' for nephrogenic etiologies. This article provides both the historical context and the rationale for this proposed name change.